Ureteral Dilatation with No Apparent Cause on Intravenous Urography: Normal or Abnormal? A Pilot Study - Vinita Rathi; Sachin Agrawal; Shuchi Bhatt; Naveen Sharma (Advances in Urology)
A pilot study was done in 18 adults to assess the significance of ureteral dilatation having no apparent cause seen on Intravenous Urography (IVU). A clinicoradiological evaluation was undertaken to evaluate the cause of ureteral dilatation, including laboratory investigations and sonography of the genitourinary tract. This was followed, if required, by CT Urography (using a modified technique). In 9 out of 18 cases, the cause of ureteral dilatation on laboratory investigations was urinary tract infection (6) and tuberculosis (3). In the remaining 9 cases, CTU identified the cause as extrinsic compression by a vessel (3), extrinsic vascular compression of the ureter along with ureteritis (2), extrinsic vascular impression on the right ureter and ureteritis in the left ureter (1), ureteral stricture (2), and ureteral calculus (1). Extrinsic vascular compression and strictures did not appear to be clinically significant in our study. Hence, ureteral dilatation without any apparent cause on intravenous urogram was found to be clinically significant in 12 out of 18 (66.6%) cases. We conclude that ureteral dilatation with no apparent cause on IVU may indicate urinary tract tuberculosis, urinary tract infection (E. coli), or a missed calculus. Thus, cases with a dilated ureter on IVU, having no obvious cause, should undergo a detailed clinicoradiological evaluation and CTU should be used judiciously.